Predictors for the Success and Survival of Entrepreneurs in the Construction Industry - Abd Hamid, Zahidy; Noor Azlinna, Azizan; Sorooshian, Shahryar (InTech, 2015)
A review of entrepreneurship literature suggests that entrepreneurial activities are the most important drivers for economic growth and corporate success, regardless of size, age or industry. Nevertheless, so far, only a few studies, if any, have considered entrepreneurship as a success factor for construction enterprises, although the importance of the construction industry to the nation's economic growth is significant. This paper reports a conceptual framework for formulating the success and survival factors of entrepreneurs in the construction industry. It also integrates four major perspectives in entrepreneurship: entrepreneurial orientation, entrepreneurial organization, entrepreneurial competencies and entrepreneurial environment. © 2015 The Author(s).